Gantry rotational motion-induced blur in cone-beam computed tomography - Krebs, J (Proc SPIE Int Soc Opt Eng, 2018)
As neuro-endovascular image-guided interventions (EIGIs) make use of higher resolution detectors, gantry rotational motion-induced blur becomes more noticeable in acquired projections as well as reconstructed images by reducing the visibility of vascular and device features whose visualization could be critical in the treatment of vascular pathology. Motion-induced blur in projections views is a function of an object’s position in the field-of-view (FOV), gantry rotational speed, and frame capture or exposure time. In this work different frame rates were used to investigate the effects of blurring from individual projections on the reconstructed image. To test the effects of these parameters on reconstructed images, a regular pattern phantom of small objects was simulated and projection views were generated at various different frame rates for a given simulated rotational velocity. The reconstruction was made using a linear interpolation of filtered backprojections. Images reconstructed from lower frame rates showed significant blurring in the azimuthal direction, increasingly worse towards the periphery of the image. However, those reconstructed from higher frame rates showed significantly less blur throughout the entire FOV. While lower frame rates could be used with slower gantry speeds this would increase the risk of voluntary or involuntary patient motion contributing to blur over the entire FOV. A high frame rate used with high gantry speeds could reliable provide images without gantry-motion blur while reducing the risk of patient-motion blur. Frame rates exceeding 2000 fps available with photon counting detectors such as the X-counter Actaeon(1) are available.